South Korea’s Interest in ASEAN+1: New Southern Policy and Peacebuilding - Rahmadanu Pradityo (Sospol : Jurnal Sosial Politik, 2022)
ASEAN as a regional organization in Southeast Asia has cooperative relations with state actors and other international organizational actors within the ASEAN+1 framework, one of which is with South Korea. ASEAN relations with South Korea experienced ups and downs due to following the dynamics that occurred on the Korean Peninsula. After the election of Moon Jae In as President of South Korea, the South Korean government emphasized its seriousness to deepen its relations with countries in Southeast Asia and India. This article explains why South Korea has again strengthened its relationship with ASEAN through the New Southern Policy. This study uses the concept of national interest based on English School thinking with a qualitative approach and literature review methods that collect data in the form of books, journals, official government websites, and scientific reports/papers. The results of this study indicate that South Korea has deepened its relationship with ASEAN to realize its national interests in the form of increasing economic cooperation which was affected by the trade war between the United States and China. In addition, South Korea's other national interest is in the form of efforts to achieve peace on the Korean Peninsula through ASEAN member countries that also have bilateral relations with North Korea.